2021
DOI: 10.3390/toxins13030218
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Distribution of Ciguatoxins in the Edible Parts of a Grouper, Variola louti

Abstract: Ciguatera fish poisoning (CFP) is one of the most frequently encountered seafood poisoning syndromes; it is caused by the consumption of marine finfish contaminated with ciguatoxins (CTXs). The majority of CFP cases result from eating fish flesh, but a traditional belief exists among people that the head and viscera are more toxic and should be avoided. Unlike the viscera, scientific data to support the legendary high toxicity of the head is scarce. We prepared tissue samples from the fillet, head, and eyes ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…Our growth dilution model assumes the concentration of ciguatoxins are homogeneous throughout the flesh of fish, and this is supported by recent findings that P-CTX-1, -2 and -3 were similarly distributed throughout the fillets of yellow-edge coronation trout ( Variola louti ) caught from Okinawa [ 158 ]. However, it is possible that the concentrations of ciguatoxins across the tissues of Spanish mackerel fillets could vary, as Li et al [ 72 ] have recently shown that much higher concentrations of ciguatoxins can accumulate in the skin compared to the muscle in goldspotted rockcod ( Epinephelus coioides ).…”
Section: Model For the Dilution Of Ciguatoxins In The Flesh Of Spanish Mackerel ( S Commerson ) Through Growthsupporting
confidence: 59%
See 1 more Smart Citation
“…Our growth dilution model assumes the concentration of ciguatoxins are homogeneous throughout the flesh of fish, and this is supported by recent findings that P-CTX-1, -2 and -3 were similarly distributed throughout the fillets of yellow-edge coronation trout ( Variola louti ) caught from Okinawa [ 158 ]. However, it is possible that the concentrations of ciguatoxins across the tissues of Spanish mackerel fillets could vary, as Li et al [ 72 ] have recently shown that much higher concentrations of ciguatoxins can accumulate in the skin compared to the muscle in goldspotted rockcod ( Epinephelus coioides ).…”
Section: Model For the Dilution Of Ciguatoxins In The Flesh Of Spanish Mackerel ( S Commerson ) Through Growthsupporting
confidence: 59%
“…However, both P-CTX-1 and P-CTX3C analogs have been detected from red bass ( Lutjanus bohar ) [ 31 ], amberjack ( Seriola dumerili ) [ 174 ] and moray eel ( Gymnothorax javanicus ) [ 22 ], showing that both families of toxins can bio-accumulate into higher trophic level fishes. Oshiro et al [ 158 ] could not detect P-CTX3C from five yellow-edge coronation trout ( Variola louti ) caught from Okinawa and contaminated with P-CTX-1, -2 and -3. As yet, P-CTX3C analogs have not been detected from dinoflagellates or fish from Australia.…”
Section: Model For the Dilution Of Ciguatoxins In The Flesh Of Spanish Mackerel ( S Commerson ) Through Growth And Depmentioning
confidence: 99%
“…Therefore, the enzyme protocol has been demonstrated as suitable for performing single determinations. According to a study by Oshiro et al (2021), CTXs are almost equally distributed within the fillet, so the error of sampling or inhomogeneity should not impair the results in the case of a single determination [51].…”
Section: Repeatabilitymentioning
confidence: 99%
“…Of note, 52-epi-54-deoxyCTX1B and 54-deoxyCTX1B were originally given the names CTX-2 and CTX-3, respectively [46]. For the record, CTX1B and the two deoxy analogs of CTX1B (Figure 4), 52-epi-54-deoxyCTX1B and 54-deoxyCTX1B, are usually found in a variety of great carnivores such as moray eels, barracudas, groupers, snappers, Spanish mackerels, or jacks in the Asia-Pacific region [43][44][45][46]51,[56][57][58][59][60][61][62][63][64]. However, these analogs were also reported in herbivorous and omnivorous coral reef fish species [53,61].…”
Section: Ciguatoxin Profiles As Assessed By Lc-ms/msmentioning
confidence: 99%